Implementasi Tradisi Dzikir Fida’ di Dusun Jetis Desa Menggoro Kecamatan Tembarak Kabupaten Temanggung - Muhammad Saefullah; Puji Wahyuningtyas; Afrokha Najia; Sari Warassati; Dian Sulistiyaningrum; Shabrina Zharfa Ghaisani; Fatchul Mubin; Puspita Ajeng Tri Rahayu; Muchamad Dias Firdhaus Irfany; Riyan Fadli; Sabrang Damar Bayu Al-azka; Ifah Fatmawati; Dita Nurul Istiqomah; Muhammad Ibadulloh Arsyada; Cindy Virginia Adella Dewantara (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Dhikr, as a spiritual practice inherent in Islamic tradition, comes in various forms and manifestations in the archipelago. One tradition that attracts attention is Dzikir Fida', a rite that is deeply rooted in the local wisdom of the people of Jetis Hamlet, Menggoro Village, Temanggung. This study examines in depth the existence of Dzikir Fida' as a manifestation of communal spirituality that lives and develops in the hamlet.Dzikir Fida', which consists of two main variants-Sughra and Kubra-is a collective practice that aims to ask for forgiveness and penance for the deceased. This tradition not only serves as an expression of condolences, but also as a means of strengthening social cohesion and reinforcing communal identity. Through the approach of religious phenomenology and symbolic anthropology, this study examines the meaning and significance of Dzikir Fida' in the socio-cultural context of the people of Jetis Hamlet.The results showed that Dzikir Fida' is not just a formal rite, but a living tradition that is lived and practiced collectively. The people of Jetis Hamlet believe that through Dzikir Fida', they not only give spiritual gifts to the deceased, but also instill noble values such as solidarity, mutual cooperation, and spirituality. This tradition becomes a medium for passing on religious values and cultural traditions from generation to generation.This research contributes to the study of the religious practices of Indonesian society, especially in the context of tradition and local wisdom. It is hoped that the results of this research can enrich the repertoire of knowledge about the phenomenology of religion and symbolic anthropology, and become a reference for the development of more in-depth studies on Dzikir Fida' and similar traditions in other regions.